The Application of MY MAMOVONO Technique to Enhance Malaysian Pre-University Students’ Mastery of the Mole Concept - Dzahari, Bibah; Kadum, Byron MC Michael (Asian Journal of Contemporary Education, 2022)
The MY MAMOVONO technique was created as an innovative way to improve pre-university students’ ability to master the mole concept. The Malaysian pre-university students mentioned that they were confused by the formulas they needed to remember. The technique required them to build a card that contained the four (4) formulas of the mole concept using their creativity. Consequently, the students performed better post-intervention than in the pre-intervention phase. The paired sample t-test analysis revealed that the mean difference (24.44) between the students’ post-intervention mean (82.78; SD = 10.46) and pre-intervention mean (58.33; SD = 7.48) is significant with p < 0.001. Moreover, the target students’ post-intervention performance was significantly better than the minimum distinction mark – the difference between the post-intervention (82.78) and minimum distinction mark (70) is 12.78 with p < 0.001. The MY MAMOVONO technique positively impacted the students’ level of understanding.